Quantitative phosphoproteomic analysis of soft and firm grass carp muscle. (15th January 2020) - Chen, Lunjian; Liu, Jie; Kaneko, Gen; Xie, Jun; Wang, Guangjun; Yu, Deguang; Li, Zhifei; Ma, Lingling; Qi, Da; Tian, Jingjing; Gong, Wangbao; Zhang, Kai; et al.
Highlights: 27 up-regulated and 22 down-regulated phosphopeptides in firm muscle of grass carp. A protein–protein interaction network including 20 phosphoproteins were obtained. Phosphorylation of myofibrillar proteins and tight junction contributed to firmness. Muscle firmness increase was also accompanied by up-regulated glycolysis pathway. Abstract: Fish muscle firmness is an important quality trait for consumer acceptance. Phosphorylation is known to change chemical and physical properties of proteins and is thus expected to affect muscle firmness, but only few such phosphoproteins have been identified. To explore phosphoproteins that affect fish muscle firmness, firm muscle (crisp grass carp) and soft muscle (ordinary grass carp) were analyzed by quantitative phosphoproteomics. We identified 27 up-regulated and 22 down-regulated phosphopeptides in crisp grass carp (ratio ≥1.5 or ≤0.667, and P -value < 0.05) and their potential upstream kinases. Protein–protein interaction analysis clustered these phosphoproteins into four groups, many of which have been suggested to impact muscle firmness and its postmortem changes: muscle fiber, connective tissue, carbohydrate metabolism and signal regulation. These results provide novel insights into the role of protein phosphorylation in fish muscle firmness and will contribute to the quality improvement of fish products.